Facing Human Capital Challenges of the 21st Century - Gonzalez, Gabriella C.; Karoly, Lynn A.; Constant, Louay; Salem, Hanine; Goldman, Charles A. (RAND Corporation, 2023)
Describes the education and labor market initiatives implemented or under way in four countries in the Arab region--Lebanon, Oman, Qatar, and the United Arab Emirates--to address the human resource issues they each face as they prepare their countries for a place in the 21st century global economy. Together, these countries highlight the variety of challenges faced by countries in the region and responses to those challenges.